2008
DOI: 10.1111/j.1365-2052.2008.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of BLV infection profiles with alleles of the BoLA‐DRB3.2 gene

Abstract: Bovine leukaemia virus (BLV) causes lymphosarcoma and persistent lymphocytosis (PL). Some MHC class II gene polymorphisms have been associated with resistance and susceptibility to the development of lymphosarcoma and PL, as well as with a reduced number of circulating BLV-infected lymphocytes. Previously, 230 BLV-infected Holstein cattle were classified into two infection profiles characterized by low and high proviral loads (LPL and HPL respectively). Here, the influence of the polymorphism at the BoLA-DRB3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
2
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 29 publications
5
128
2
18
Order By: Relevance
“…In the present investigation we found a significant number of animals carrying this allele in our herd, compared to the population of Holstein in Argentina (TAKESHIMA et al, 2015); however, no association could be established between allele BoLA DRB3.2*1101 and BLV PVL. In the literature BoLA DRB3.2*0902 (or *11 determined by PCR-RFLP) allele was most strongly associated with PL resistance or LPVL profile in Holstein cattle (XU et al, 1993;ZANOTTI et al, 1996;MIRSKY et al, 1998;JULIARENA et al, 2008;PANEI et al, 2009;MIYASAKA et al, 2013). In the present investigation we did not find this association, which could be due to a lower frequency of presentation of *0902 allele in this herd in comparison with the Argentinean Holstein populations (4.21% vs 6.4%, respectively) (TAKESHIMA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present investigation we found a significant number of animals carrying this allele in our herd, compared to the population of Holstein in Argentina (TAKESHIMA et al, 2015); however, no association could be established between allele BoLA DRB3.2*1101 and BLV PVL. In the literature BoLA DRB3.2*0902 (or *11 determined by PCR-RFLP) allele was most strongly associated with PL resistance or LPVL profile in Holstein cattle (XU et al, 1993;ZANOTTI et al, 1996;MIRSKY et al, 1998;JULIARENA et al, 2008;PANEI et al, 2009;MIYASAKA et al, 2013). In the present investigation we did not find this association, which could be due to a lower frequency of presentation of *0902 allele in this herd in comparison with the Argentinean Holstein populations (4.21% vs 6.4%, respectively) (TAKESHIMA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the infection with BLV in Holstein breed, several studies have shown that the susceptibility to PL was associated with the presence of BoLA DRB3*0101, *1501 or 03, *1101 or 02, and *1201 (XU et al, 1993;ZANOTTI et al, 1996;MIRSKY et al, 1998;JULIARENA et al, 2008;PANEI et al, 2009;NIKBAKHT BRUJENI et al, 2016). In the present study, BoLA DRB3*1201 was the most significantly associated with HPVL (p = 0.0111), and this might be due to the fact that its frequency in the investigated population was about one third higher than in other Argentinean Holstein populations (11.21% vs 7.3%, respectively) (TAKESHIMA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations